Pierre le Mangeur ou Pierre de Troyes: Maître du XIIe siècle. Edited by Gilbert Dahan - Evans, Gillian (The journal of theological studies, 2013)
These papers on Peter Comestor are the fruits of a conference held in Troyes in 2011. They do much to round out our picture of this figure, well known and highly ‘rated’ in his time, but not in the mainstream of later medieval academic trends. It begins with two essays setting him in context, on his life as a canon of Troyes before his ‘Paris period’ and on his contribution to the development of medieval theology. There follow three essays on his exegetical work, including his ‘Jewish sources’. Could the Comestor have had direct contact with Jewish scholarship in his time at Troyes? If so, he must be added to a short list of twelfth-century scholars whose access to Old Testament Hebrew could be important.